Isolation and Screening of Enzymatic Hydrolysis of Starch by Enzyme Amylase from Soil Isolate Aspergillus Niger - Neha Baqai (RADS Journal of Biological Research & Applied Science, 2015)
Amylase has become the most promising enzyme in the industrial field due to its economical values and high catalytic rate. This class of enzyme constitutes approximately 25–30% of the enzyme stock around the world. It is commercially used for various purposes such as: hydrolysis of starch, resizing of textile fabrics, in pharmaceutical industries, in food industries, in paper industry, in detergent industry etc. α-Amylase can be produced by multitudunial sources i.e.plants, animals and microorganism but fungal amylase has become a new field of interest for the researchers.20 different soil samples were collected for the isolation of Aspergillus.niger. Selected strains from soil samples are subcultured on SDA agar and screened their ability for producing α- amylase by starch hydrolysis on a starch agar, clear sharp zones are observed from all the collected samples showing a clear hydrolysis of starch around the colonies. These fungal species are further processed for solid state fermentation in which wheat bran is used as a substrate from agro industrial wastes, resulted in high amount of production of enzyme amylase. Amylases hydrolyze complex molecules of starch into small oligosaccharides in step wise pattern. The determination of reducing sugar is done by Dinitrosalicylic acid method and observed by spectrophotometry at 575nm. A confirmatory starch-iodine test is also done, a drop of iodine is added in the tubes containing starch which turns the color blue but by adding raw enzyme that have been collected from the supernatant disappears the blue color which evident the production of enzyme α-amylase.